Effects of replacing soy bean meal with dry distillers grain with solubles - Lewis, Peyton M.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
Goat populations are climbing rapidly both in the United States and other developing countries. There is a lack of research on the effects of increasing dried distiller grain in a goats’ diet when the staple of their diet is soybean meal. Forty-eight Boer goat kids around 70d of age were utilized in a randomized design to determine if soybean meal can be effectively replaced with dry distiller’s grain with solubles (DDGS). The Boer goat kids were evaluated for DDGS impact on carcass traits (HCW, Loin eye area, Loin eye depth, Back fat, Body wall thickness), ADG and G:F. With sixteen pens and three goats per pen the goats were randomly assigned one of the four treatments. With a 14d step up ration to ensure a smooth transition, the goats were assigned to diets with SBM replaced by 0% DDGS, 33% DDGS, 66% DDGS, 100% DDGS. Goat weight and feeder weight were collected every seven days for forty-seven days. On day forty-seven two kids from every pen were randomly selected to be sent to slaughter for the evaluation of their carcass parameters. The carcass traits collected were not statistically significant (P=0.478). Trends were able to be observed but scientifically we could not conclude any differences. Average daily gain yielded no statistically different results between treatments (P=0.092). The goats that were fed 66% DDGS and 100% DDGS had greater feed efficiency than those on the diets of 33% DDGS or 0%. The statistical evidence for carcass traits and ADG indicates that soybean meal can be effectively replaced with DDGS without altering the carcass traits of the goat. In summary, goats can effectively be feed a diet of up to 100% DDGS with solubles as a replacement for soy bean meal with no notable statistical differences in the carcass traits collected.
Keywords: Spring 2018